WORK FATIGUE: AN ANALYTICAL STUDY OF WORKERS AT PT. DISTRIBUSI ENERGI MANDIRI, MAKASSAR CITY, INDONESIA - Asri Asri; Silvester Matrutty; Andi Alim; Asriani Minarti S (Poltekkes Kemenkes Semarang, 2023)
Work fatigue is a work-related tiredness that can become severe, inflict sleeping problems, and even threaten workers’ lives. The International Labor Organization (ILO) recorded annual deaths of approximately two million workers due to fatigue-induced accidents. The authors studied the factors promoting work fatigue in workers at PT. Distribusi Energi Mandiri (DEM) using an analytic survey method. This involved the entire workers as the study population and a questionnaire as the data collection method. In our findings, the chi-square test analysis revealed that work duration (p= 0.718 ( 0.05)), age (p= 1.000 ( 0.05)), and work posture (p= 0.176 ( 0.05)) have no relationships with work fatigue, but not with workload (p= 0.003 ( 0.05)). We, therefore, suggested that the management of PT. DEM continues and maintains the ongoing work duration, but provides assistive devices to workers with excessive workloads. In addition, it is necessary to supervise them to change body positions, stretch up and rest periodically during work. We advised workers to take proper breathing and intake, along with paying attention to occupational health and safety.